2022
DOI: 10.1007/s12035-022-02885-5
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside Improves Cognitive Impairment by Inhibiting Aβ Deposition Through the PI3K/AKT/Nrf2/PPARγ Signaling Pathways in APP/PS1 Mice

Abstract: Echinacoside (ECH), a phenylethanoid glycoside, has protective activity in neurodegenerative disease, including anti-inflammation and antioxidation. However, the effects of ECH in Alzheimer’s disease (AD) are not very clear. This present study investigates the role and mechanism of ECH in the pathological process of AD. APP/PS1 mice treated with ECH in 50 mg/kg/day for 3 months. Morris water maze, nesting test, and immunofluorescence staining used to observe whether ECH could improve AD pathology. Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Compounds with high response values in the chemical profile, such as aucubin, exhibit neuroprotective, anti-neuroinflammatory, and antioxidant properties [57]. In addition, echinacoside has been reported to improve cognitive impairment by inhibiting Aβ deposition through the PI3K/AKT/Nrf2/PPARγ signaling pathways in APP/PS1 mice [58]. Acteoside, isoacteoside, and echinacoside exert neuroprotective effects on H 2 O 2 -induced apoptosis in PC12 cells via the Nrf2/ARE pathway [59].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds with high response values in the chemical profile, such as aucubin, exhibit neuroprotective, anti-neuroinflammatory, and antioxidant properties [57]. In addition, echinacoside has been reported to improve cognitive impairment by inhibiting Aβ deposition through the PI3K/AKT/Nrf2/PPARγ signaling pathways in APP/PS1 mice [58]. Acteoside, isoacteoside, and echinacoside exert neuroprotective effects on H 2 O 2 -induced apoptosis in PC12 cells via the Nrf2/ARE pathway [59].…”
Section: Discussionmentioning
confidence: 99%
“…Following Nrf2 siRNA transfection and LY294002 treatment, genistein cannot stimulate HO‐1 to exert the neuroprotective effects on Ab25‐35‐treated SH‐SY5Y cells (Yi et al., 2021). Echinacoside reduces senile plaque deposition in brains by activating the PI3K/AKT/Nrf2/PPARγ pathway, which improves cognitive function and represses inflammatory response and oxidative stress in AD (Qiu & Liu, 2022). In brief, this study discovered for the first time that hUCMSC‐Evs alleviated the neurological injury of VaD rats by activating the PI3K/AKT/Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Echinacoside (ECH) is the most active component of C. tubulosa. Previous studies have shown ECH might be potentially promising for the treatment of depressive disorders, vascular dementia, cerebral ischemia, Parkinson's disease, and AD [28][29][30][31][32]. ECH can freely cross the blood-brain barrier, exhibiting neuroprotective, anti-oxidative, anti-neuroinflammatory properties, and regulating apoptosis and autophagy [33].…”
Section: Introductionmentioning
confidence: 99%